Project management theory and practice - Richardson, Gary L.; Jackson, Brad M. (CRC Press, 2019)
Project Management: Theory and Practice, Third Edition gives students a broad and real flavor of project management. Bringing project management to life, it avoids being too sterilely academic and too narrowly focused on a particular industry view. It takes a model-based approach towards project management commonly used in all industries. The textbook aligns with the latest version of the Project Management Institute's Project Management Body of Knowledge (PMBOK®) Guide, which is considered to be the de facto standard for project management. However, it avoids that standard's verbiage and presents students with readable and understandable explanations. Core chapters align with the Project Management Institute's model as well as explain how this model fits real-world projects. The textbook can be used as companion to the standard technical model and help those studying for various project management certifications. The textbook takes an in-depth look at the following areas important to the standard model: Work Breakdown Structures (WBS)Earned Value Management (EVM)Enterprise project managementPortfolio management (PPM)Professional responsibility and ethicsAgile life cycleThe text begins with a background section (Chapters 1-9) containing material outside of the standard model structure but necessary to prepare students for the 10 standard model knowledge areas covered in the chapters that follow. The text is rounded out by eight concluding chapters that explain advanced planning approaches models and projects' external environments. Recognizing that project management is an evolving field, the textbook includes section written by industry experts who share their insight and expertise on cutting-edge topics. It prepares students for upcoming trends and changes in project management while providing an overview of the project management environment today. In addition to guiding students through current models and standards, Project Management: Theory and Practice, Third Edition prepares students for the future by stimulating their thinking beyond the accepted pragmatic view.- Resumé vydavatel
9.5.6 Standard Architectures.
Keywords: projektový management; project management; elektronické knihy; monografie; electronic books; monographs